2015
DOI: 10.3906/sag-1407-69
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac factors affecting the success of vardenafil in erectile dysfunction

Abstract: Background/aim: To evaluate the predictability of vardenafil success in patients with erectile dysfunction (ED) by using cardiological tests. Materials and methods:Patients diagnosed with ED who did not benefit from lifestyle changes (n = 68) were evaluated with an abridged 5-item version of the International Index of Erectile Function (IIEF-5). The pretreatment and posttreatment IIEF-5 scores were compared with pretreatment data obtained from cardiological examinations.Results: When pretreatment scores were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Some authors have shown cardioprotective effects through regulation of endothelial dysfunction with continuous use of PDE 5 inhibitors, and it has also been shown that there may be positive hemodynamic effects in patients with HF [30]. A recent study showed that the E 0 /A 0 ratio as an indicator of diastolic functions was positively correlated with IIEF-5 scores before treatment and negatively correlated with the beneficial effect of vardenafil therapy [31]. However, these studies are short-lived.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have shown cardioprotective effects through regulation of endothelial dysfunction with continuous use of PDE 5 inhibitors, and it has also been shown that there may be positive hemodynamic effects in patients with HF [30]. A recent study showed that the E 0 /A 0 ratio as an indicator of diastolic functions was positively correlated with IIEF-5 scores before treatment and negatively correlated with the beneficial effect of vardenafil therapy [31]. However, these studies are short-lived.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the patients were advised to use 10 mg vardenafil tablet before sexual intercourses for two months (one tablet for each sexual intercourse and use of at least 8 pills within this duration). The patients who used at least 8 ten-milligram vardenafil pills within this duration (maximum 12 pills) were reevaluated in respect to ED severity by the help of IIEF-5 at the end of two-month vardenafil treatment [ 4 ]. The difference between the pretreatment and posttreatment IIEF-5 values was accepted as ΔIIEF-5.…”
Section: Methodsmentioning
confidence: 99%
“…Until now, there has not been any guideline providing special indication for particular type of PDE5Is. Although there have been few studies searching predictors of PDE5I success, the physicians still do not have clinical parameters defining subjects who may benefit from PDE5Is [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%